PARTISIPASI MASYARAKAT LOKAL DALAM PENGEMBANGAN DTW AIR TERJUN GITGIT DI KABUPATEN BULELENG - Nyoman Gede Maswiartha (Jurnal Ilmiah Hospitality Management, 2018)
The purpose of this study was to determine the form of local community participation and the benefits of community participation in the development of DTW Gitgit Waterfall. This study uses qualitative and quantitative methods. The data analysis technique is used by questioner with a Likert scale. The results of this study form the participation of local communities in the development of the DTW of Gitgit Waterfall mostly involved, including forms of social participation with a score of 3.69 (often), involvement in skills and skills participation with a score of 3.5 (often), involvement in labor participation with score of 3.44 (quite often), involvement in the form of ideas participation with a score of 3.32 (quite often), and involvement in the form of property participation with a score of 3.13 (quite often). The benefits of gitgit waterfall community participation obtained by the local community in the development of tourist attraction in the form of an increase in terms of socio-cultural, amounting to 89%, an economic aspect of 97% and in terms of the environment by 86%.Â Keywords: community participation, tourism development, Gitgit Waterfall